Factors Affecting Maize Productivity: In Case of Bedele District of Buno Bedele Zone, Oromia Regional State, Ethiopia - Dube, Bati; Abebe, Tilaye (Discoveries in Agriculture and Food Sciences, 2022)
Though agriculture remains to be the most important sector of the Ethiopian economy, its performance has been disappointing and food production has been lagging behind population growth. This gap between demand for and supply of food can be reduced by improving crop production and productivity. As maize is a significant contributor to the Ethiopian economy, increasing production and productivity in maize production could be taken as an important step in attaining food security. This study was conducted in Bedele district of Buno Bedele zone of Oromia National Regional State with the aim of identifying factors affecting the productivity of maize production. This study used cross sectional data which was collected from a total of 174 farm households which were randomly and proportionally selected from 4kebeles of the Woreda using two stage sampling technique. The primary data were collected through individual interviews of respondents using semi-structure questionnaire. Secondary data was collected from different relevant literatures such as district reports, publications, journals and other documents relevant for the study. Descriptive statistics and Econometric model were used to assess the collected data. The result of Descriptive statistics indicated that the mean amount of maize produced by households in quintal per hectare is about 19.76 quintal. Results of Cobb- Douglas production function revealed that Variability of weather condition, Extension Contact, Land allocated for maize, Mode of sowing, Amount of fertilizer used, Farm Income, labor cost, Number of Oxen, and educational level of household head positively and significantly affected the productivity of maize production. Whereas Soil fertility, occurrence of pests and diseases, over cultivation are negatively and significantly affected the productivity of maize production. Therefore, attention should be given to major factors that affect the productivity of maize production to increase production and productivity of maize.